The Tech Professional's Guide to Communicating in a Global Workplace Adapting Across Cultural and Gender Boundaries - Wells, April (Apress, 2018)
Information technologists are increasingly being made part of global teams, and are confronting the challenges of communicating across a variety of linguistic and cultural boundaries. This book helps you rise to those challenges by helping you know what to say, what not to say, and even where to sit in meetings and in social situations. People talk about the increasingly global nature of work, and that is one way to look at communicating across cultures-from one country or region to another. But what about the differences in culture between various groups at the local level? What about developers to DBAs? IT staff to business people? Women to men? People approaching retirement to people coming into the organization fresh out of college? There are innumerable different cultures within an organization, and it's to your advantage to be able to adapt and communicate effectively and efficiently across all of them. The author provides her personal experiences and shares anecdotes as well as lessons learned, key takeaways, and references for further reading. Whether it is face to face, over the phone, via email or instant messenger, or in a presentation, meeting, or report, the ability to communicate effectively is critical. Words hold power, and understanding their power and being able to effectively use words in the right way for the right audience is important to everyone's reputation and career. What You'll Learn: Concisely communicate with the right audience in the right way Write emails that are understood and get the results you want Improve personal reputation as an effective communicator Communicate across cultural boundaries without offending Present the desired impression in business situations Grow professionally by adjusting your communication style.